Method for preparing double-sided conductive sheet
By optimizing the material formulation and process flow, the double-layer extrusion injection molding process and surface-covered superconducting nanocarbon black solves the problems of unstable conductivity, difficulty in balancing mechanical properties and conductivity, complex preparation processes and high costs in the preparation of double-sided conductive sheets, and achieves the dual advantages of high performance and low cost.
Patent Information
- Application Number
- CN202510053268.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-14
AI Technical Summary
The existing double-sided conductive sheet preparation technology faces problems such as unstable conductivity, difficulty in balancing mechanical properties and conductivity, complex preparation processes and high costs, and it is difficult to meet the dual demands of performance and cost in the high-tech field.
By optimizing the material formula and process flow, using a double-layer extrusion injection molding process, rationally selecting raw materials such as polystyrene, rubber and conductive masterbatch, and improving the conductive properties through surface-coated superconducting nanocarbon black.
It realizes excellent conductivity, good mechanical strength and heat resistance of double-sided conductive sheets, as well as simplified production processes and reduced production costs, and is suitable for electronic equipment and automobile industry and other fields.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive plastic sheets, in particular to a method for preparing a double-sided conductive sheet. Background Art
[0002] With the development of modern electronic equipment, the automotive industry, and other high-tech fields, the demand for functional materials is increasing, and conductive sheets have become key materials in many applications. Conductive sheets can conduct electric current while being lightweight and high-strength, so they are widely used in electromagnetic shielding, conductive connections, electrostatic protection, and other fields. However, traditional conductive sheets usually only have single-sided conductivity and cannot meet the needs of double-sided conductivity in some specific scenarios, such as complex circuit designs and components that require simultaneous conduction, heat transfer, or shielding.
[0003] Double-sided conductive sheets can effectively improve current conduction efficiency, reduce the use of connectors, simplify product design, and improve overall performance because both sides of the double-sided conductive sheet have conductive properties. In the electronics industry, double-sided conductive sheets can be used for multi-layer circuit board connections, electromagnetic compatibility design, and flexible electronic products; in the automotive industry, it can be used for automotive grounding components, sensor protection, and battery management systems. However, the existing preparation technology of double-sided conductive sheets faces many challenges in practical applications:
[0004] Instability of conductive properties: Currently, the methods for preparing double-sided conductive sheets mostly rely on surface coating or filling with conductive particles, which often leads to poor adhesion of the conductive layer or uneven distribution of conductive particles. This unevenness makes the material prone to performance degradation or failure in actual use, affecting reliability.
[0005] The difficulty of balancing mechanical properties and conductive properties: High conductivity usually requires a higher content of conductive fillers, but this will significantly reduce the mechanical properties of the material, such as tensile strength, toughness, etc. This performance balance problem has become an important factor limiting the promotion of double-sided conductive sheets.
[0006] Limitations of complex preparation process: The existing preparation process of double-sided conductive sheets usually requires multiple steps, such as conductive coating, sintering or lamination extrusion, which is complex, energy-intensive, and has a low yield rate. In addition, the interface of multi-layer materials often has problems such as poor adhesion and delamination, which is not conducive to long-term use.
[0007] Cost issue: In traditional processes, the high content of conductive masterbatch and the use of high-precision equipment lead to high production costs, limiting the application scope of double-sided conductive sheets in the mid- and low-end markets.
[0008] In view of the above problems, a new method for preparing double-sided conductive sheets is urgently needed. This method can ensure the conductive properties while having excellent mechanical properties and processing properties, and has the advantages of simple preparation process, low energy consumption and controllable cost. Summary of the invention
[0009] The present invention aims at the above problems and proposes a new method for preparing double-sided conductive sheets by optimizing material formula design and process flow. By rationally selecting raw materials and developing double-layer extrusion injection molding process, a balance between material performance and cost is achieved, providing a new technical solution for the application of conductive sheets in electronic equipment, automotive industry and other fields.
[0010] A method for preparing a double-sided conductive sheet, the operating steps of which are:
[0011] A side: 70-80 parts of polystyrene, 1-5 parts of rubber and 0.5-2 parts of color powder are dried and mixed evenly to obtain the A side material;
[0012] B side: 5-9 parts of polystyrene, 4-8 parts of conductive masterbatch and 0.1-0.5 parts of rubber are dried and mixed evenly to obtain B side material;
[0013] The A-side material and the B-side material are extruded in a double-layer extruder, dried at 80-100° C. for 1-1.5 hours, and injection molded to obtain a double-sided conductive sheet.
[0014] In some embodiments, the A-side and B-side rubbers are selected from at least one of thermoplastic polyurethane rubber, thermoplastic styrene-butadiene rubber, ethylene-propylene-diene monomer rubber, and nitrile rubber.
[0015] In some embodiments, the toner is selected from one of black, blue, yellow, orange, red, and green.
[0016] In some embodiments, the conductive masterbatch is surface-coated superconducting nano-carbon black, and its preparation method is as follows:
[0017] S1: by mass, 18-36 parts of 2-(3-amino-1,1-dioxythiophene-3-yl)acetic acid (CAS: 1785076-11-0), 3-6 parts of nickel nitrate, and 200-300 parts of water are stirred at 50-60° C. for 100 to 150 minutes; water is distilled off to obtain a 2-(3-amino-1,1-dioxythiophene-3-yl)acetic acid / nickel complex;
[0018] S2: 100-120 parts of superconducting nano carbon black, 2-5 parts of allyl silane treating agent, 1000-1200 parts of DMF, stirring and reacting at 70-80° C. for 100 to 150 minutes;
[0019] S3: Add 4-7 parts of 2-(3-amino-1,1-dioxythiophene-3-yl)acetic acid / nickel complex and 0.05-0.5 parts of diamine tetrachlorotitanate (CAS No.: 15719-81-0), stir and react at 70-80°C for 60 to 100 minutes; filter and dry to obtain surface-coated superconducting nano-carbon black.
[0020] In some embodiments, the extrusion process conditions of the double-layer extruder are: the feeding section temperature is 160-180°C, the compression section temperature is 180-200°C, the homogenization section temperature is 215-235°C, the die temperature is 205-225°C, the extrusion speed is 250-350r / min, and the feeding speed is 10-14r / min.
[0021] In some embodiments, the injection molding process conditions are: the feeding section temperature is 160-180°C, the middle section temperature is 210-230°C, and the gate temperature is 205-225°C.
[0022] Reaction mechanism of superconducting nanocarbon black:
[0023] After the superconducting nano carbon black is treated with an allyl silane treatment agent, the superconducting nano carbon black containing allyl groups is obtained; then, the superconducting nano carbon black containing allyl groups is subjected to an amino-allyl addition reaction with a 2-(3-amino-1,1-dioxythiophene-3-yl)acetic acid / nickel complex, and the diamine tetrachlorotitanate and the superconducting nano carbon black containing allyl groups are subjected to an amino-allyl addition reaction. The tetrachlorotitanate coated with the thiophene-3-ylacetic acid / nickel complex and the tetrachlorotitanate complex is obtained; and the conductivity of the double-sided conductive sheet is improved.
[0024] Superconducting nano carbon black technology effects:
[0025] 1) Improved conductivity: The titanium element in diammine tetrachlorotitanate has multiple oxidation states, which can promote the transfer and transmission of electrons. When it is combined with allyl-containing superconducting nanocarbon black, it may improve the electron mobility and conductivity of the material by forming stable chemical bonds or charge transfer complexes.
[0026] 2) Reduce resistance: Superconducting nanocarbon black itself has good conductivity, but it may still have resistance under certain conditions. The addition of diammine tetrachlorotitanate may further reduce resistance by improving the microstructure and electron distribution of the material.
[0027] The present invention discloses a method for preparing a double-sided conductive sheet. Compared with the prior art, the present invention has the following significant effects.
[0028] 1) Excellent electrical conductivity: Both side A and side B have electrical conductivity and can be used in applications requiring higher electrical conductivity.
[0029] 2) Good mechanical strength and heat resistance: The produced sheet has good tensile strength and high temperature resistance, and can adapt to different working environments.
[0030] 3) Good processing performance: Through double-layer extrusion and injection molding process, the production process is simple, efficient, product size is stable and quality is reliable. DETAILED DESCRIPTION
[0031] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description in combination with embodiments and comparative examples.
[0032] 1. Tensile yield strength test: Conduct tensile test in accordance with GB / T 1040 to test the maximum tensile strength of the material in MPa.
[0033] 2. Surface resistance test: Use the four-point probe method to test the surface resistance of surface A and surface B respectively, the unit is Ω / sq.
[0034] 3. Conduct heat deformation temperature test in accordance with GB / T 1634, the unit is ℃.
[0035] Embodiment 1:
[0036] In the process of preparing the double-sided conductive sheet, 75g polystyrene, 3g thermoplastic polyurethane rubber and 1g black color powder are used for the A side, and the A side material is obtained after being mixed evenly; 6g polystyrene, 4g conductive masterbatch and 0.3g ethylene-propylene-diene monomer rubber are used for the B side, and the B side material is obtained after being mixed evenly. The two materials are extruded in a double-layer extruder, and the extrusion process conditions are set as a feeding section temperature of 170°C, a compression section temperature of 190°C, a homogenization section temperature of 225°C, a die temperature of 215°C, an extrusion speed of 300r / min, and a feeding speed of 12r / min. The extruded material is dried at 90°C for 1.25 hours, and then injection molded. The injection molding process conditions are a feeding section temperature of 170°C, a middle section temperature of 220°C, and a gate temperature of 215°C, and finally a double-sided conductive sheet is obtained.
[0037] The preparation method of the conductive masterbatch is as follows: 27g of 2-(3-amino-1,1-dioxythiophene-3-yl)acetic acid, 4.5g of nickel nitrate and 250g of water are mixed, and the reaction is stirred at 55°C for 120 minutes. After the reaction is completed, the water is removed by distillation to obtain a 2-(3-amino-1,1-dioxythiophene-3-yl)acetic acid / nickel complex. Then, 110g of superconducting nano-carbon black, 3g of allyl silane treatment agent and 1100g of DMF are mixed, and the reaction is stirred at 75°C for 130 minutes. Then, 5g of the above-mentioned complex and 0.3g of diamine tetrachlorotitanate are added to the reaction system, and the reaction is continued to be stirred at 75°C for 80 minutes. Finally, the surface-coated superconducting nano-carbon black is obtained by filtering and drying.
[0038] Embodiment 2:
[0039] In the process of preparing the double-sided conductive sheet, 78g polystyrene, 2g thermoplastic styrene-butadiene rubber and 1.5g blue color powder are used for the A side, and the A side material is obtained after being mixed evenly; 5g polystyrene, 5g conductive masterbatch and 0.2g nitrile rubber are used for the B side, and the B side material is obtained after being mixed evenly. The A side and B side materials are extruded in a double-layer extruder according to the following process conditions: feeding section temperature 165℃, compression section temperature 185℃, homogenization section temperature 215℃, die temperature 205℃, extrusion speed 275r / min, feeding speed 11r / min. The extruded material is dried at 85℃ for 1.5 hours, and then injection molded. The injection molding conditions are feeding section temperature 165℃, middle section temperature 215℃, gate temperature 205℃, and finally a double-sided conductive sheet is obtained.
[0040] The preparation method of the conductive masterbatch is as follows: 36g of 2-(3-amino-1,1-dioxythiophene-3-yl)acetic acid, 6g of nickel nitrate and 300g of water are stirred and reacted at 60°C for 150 minutes, and then the water is distilled off to obtain a complex. Then, 120g of superconducting nano-carbon black, 5g of allyl silane treatment agent and 1200g of DMF are mixed and stirred and reacted at 80°C for 150 minutes. Next, 7g of the complex and 0.5g of diamine tetrachlorotitanate are added to the reaction system, and the stirring reaction is continued at 80°C for 100 minutes. Finally, the surface-coated superconducting nano-carbon black is obtained through filtering and drying steps.
[0041] Embodiment 3:
[0042] In the process of preparing the double-sided conductive sheet, the A-side material is composed of 72g polystyrene, 4g thermoplastic polyurethane rubber and 0.8g yellow toner, which are mixed evenly; the B-side material is composed of 7g polystyrene, 6g conductive masterbatch and 0.4g ethylene-propylene-diene monomer rubber, which are also mixed evenly. The two materials are extruded in a double-layer extruder according to the following process conditions: feeding section temperature 180℃, compression section temperature 200℃, homogenization section temperature 235℃, die temperature 225℃, extrusion speed 350r / min, feeding speed 14r / min. The extruded material is dried at 80℃ for 1 hour and then injection molded. The injection molding conditions are feeding section temperature 180℃, middle section temperature 230℃, gate temperature 225℃, and finally a double-sided conductive sheet is obtained.
[0043] The preparation method of the conductive masterbatch is as follows: 18g of 2-(3-amino-1,1-dioxythiophene-3-yl)acetic acid, 3g of nickel nitrate and 200g of water are mixed, stirred and reacted at 50°C for 100 minutes, and the water is distilled off to obtain a complex. Next, 100g of superconducting nano-carbon black, 2g of allyl silane treatment agent and 1000g of DMF are mixed, and stirred and reacted at 70°C for 100 minutes. Then, 4g of the complex and 0.05g of diamine tetrachlorotitanate are added to the reaction system, and the stirring reaction is continued at 70°C for 60 minutes. Finally, after filtering and drying, the desired surface-coated superconducting nano-carbon black is obtained.
[0044] Embodiment 4:
[0045] In the process of preparing the double-sided conductive sheet, 70g polystyrene, 1g thermoplastic styrene-butadiene rubber and 2g orange color powder are used for the A side, and the A side material is obtained after being mixed evenly; 9g polystyrene, 8g conductive masterbatch and 0.1g thermoplastic polyurethane rubber are used for the B side, and the B side material is obtained after being mixed evenly. The two materials are extruded in a double-layer extruder according to the following process conditions: feeding section temperature 160℃, compression section temperature 180℃, homogenization section temperature 220℃, die temperature 210℃, extrusion speed 250r / min, feeding speed 10r / min. The extruded material is dried at 100℃ for 1 hour, and then injection molded. The injection molding conditions are feeding section temperature 160℃, middle section temperature 210℃, gate temperature 210℃, and finally a double-sided conductive sheet is obtained.
[0046] The preparation method of the conductive masterbatch is as follows: 27g of 2-(3-amino-1,1-dioxythiophene-3-yl)acetic acid, 4.5g of nickel nitrate and 275g of water are stirred and reacted at 52.5°C for 135 minutes, and then the water is distilled off to obtain a complex. Then, 115g of superconducting nano-carbon black, 4g of allyl silane treatment agent and 1150g of DMF are mixed and stirred and reacted at 77.5°C for 140 minutes. Then, 6g of the complex and 0.2g of diamine tetrachlorotitanate are added to the reaction system, and the stirring reaction is continued at 77.5°C for 90 minutes. Finally, the desired surface-coated superconducting nano-carbon black is obtained through filtering and drying steps.
[0047] Comparative Example 1
[0048] This comparative example is used to compare and illustrate the double-sided conductive sheet disclosed in the present invention. Its raw materials include most of the components and operating steps in Example 1, and the difference is that the conductive masterbatch is superconducting nano-carbon black instead of surface-coated superconducting nano-carbon black.
[0049] Comparative Example 2
[0050] This comparative example is used to compare and illustrate the double-sided conductive sheet disclosed in the present invention. Its raw materials include most of the components and operating steps in Example 1, and the difference is that diamine tetrachlorotitanate is not added in the preparation process of the conductive masterbatch.
[0051] Comparative Example 3
[0052] This comparative example is used to compare and illustrate the double-sided conductive sheet disclosed in the present invention. Its raw materials include most of the components and operating steps in Example 1, except that 2-(3-amino-1,1-dioxythiophene-3-yl)acetic acid is not added during the preparation of the conductive masterbatch.
[0053] The test results are shown in Table 1.
[0054] Table 1
[0055] Tensile strength MPa Surface resistance Ω / sq Heat deformation temperature℃ Example 1 62.5 <![CDATA[5.8×10 2 ]]> 112.5 Example 2 63.4 <![CDATA[5.3×10 2 ]]> 114.0 Example 3 61.9 <![CDATA[4.9×10 2 ]]> 116.6 Example 4 62.8 <![CDATA[4.2×10 2 ]]> 117.3 Comparative Example 1 60.7 <![CDATA[1.1×10 5 ]]> 105.5 Comparative Example 2 61.4 <![CDATA[2.9×10 4 ]]> 110.6 Comparative Example 3 61.0 <![CDATA[4.7×10 4 ]]> 108.4
[0056] The test results show that the technical solution of the present invention significantly improves the overall performance of the conductive sheet by optimizing the material formula and process conditions, proving that it has broad practical application value.
[0057] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a double-sided conductive sheet, the operating steps of which are: A side: 70-80 parts of polystyrene, 1-5 parts of rubber and 0.5-2 parts of color powder are dried and mixed evenly to obtain the A side material; B side: 5-9 parts of polystyrene, 4-8 parts of conductive masterbatch and 0.1-0.5 parts of rubber are dried and mixed evenly to obtain B side material; The A-side material and the B-side material are extruded in a double-layer extruder, dried at 80-100° C. for 1-1.5 hours, and injection molded to obtain a double-sided conductive sheet; The conductive masterbatch is a surface-coated superconducting nano carbon black, and its preparation method is as follows: S1: by mass, 18-36 parts of 2-(3-amino-1,1-dioxythiophene-3-yl)acetic acid, 3-6 parts of nickel nitrate, and 200-300 parts of water are stirred at 50-60° C. for 100 to 150 minutes; water is distilled off to obtain a 2-(3-amino-1,1-dioxythiophene-3-yl)acetic acid / nickel complex; S2: 100-120 parts of superconducting nano carbon black, 2-5 parts of allyl silane treating agent, 1000-1200 parts of DMF, stirring and reacting at 70-80° C. for 100 to 150 minutes; S3: Add 4-7 parts of 2-(3-amino-1,1-dioxythiophene-3-yl)acetic acid / nickel complex and 0.05-0.5 parts of diamine tetrachlorotitanate, stir and react at 70-80° C. for 60 to 100 minutes; filter and dry to obtain surface-coated superconducting nano-carbon black.
2. The method for preparing a double-sided conductive sheet according to claim 1, characterized in that: The A-side and B-side rubbers are selected from at least one of thermoplastic polyurethane rubber, thermoplastic styrene-butadiene rubber, ethylene-propylene-diene monomer rubber, and nitrile rubber.
3. The method for preparing a double-sided conductive sheet according to claim 1, characterized in that: The toner is selected from one of black, blue, yellow, orange, red and green.
4. The method for preparing a double-sided conductive sheet according to claim 1, characterized in that: The extrusion process conditions of the double-layer extruder are as follows: the temperature of the feeding section is 160-180°C, the temperature of the compression section is 180-200°C, the temperature of the homogenization section is 215-235°C, the die temperature is 205-225°C, the extrusion speed is 250-350r / min, and the feeding speed is 10-14r / min.
5. The method for preparing a double-sided conductive sheet according to claim 1, characterized in that: The injection molding process conditions are as follows: the temperature of the feeding section is 160-180°C, the temperature of the middle section is 210-230°C, and the gate temperature is 205-225°C.